The Level of Digitalization before and During the Covid-19 Pandemic in Republic of North Macedonia (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Information and communication technologies (ICT) play a leading role in the transformation of national economies. Their use covers various spheres of economic activities and creation of new opportunities for socio-economic development. Digital innovation, through digital technologies and digital business models, inevitably leads to organizational change paving the way for the digital transformation of organizations, bringing sustainable implications for all business aspects. Digital transformation is a prerequisite for active inclusion of Macedonian businesses in the European market whose digital form is subject to continuous monitoring and development by EU institutions. The Covid-19 pandemic had a significant impact on the economy and society. It has significantly changed the role and perception of digitalization and accelerated its pace. Digital technologies have played an important role in the coordinated response to Covid-19 at EU level. Digital technologies are essential for sustaining economic and social life during a pandemic. They will be the key to a successful transition to a sustainable, post-pandemic economy and society. Investments in digital technologies, infrastructure and processes will make the Macedonian economy more competitive globally. The main aim of this paper will to elaborate the key indicators for measuring the level of digitalization in the Republic of North Macedonia. A comparative analysis of the level of digital transformation in small and medium enterprises before and during the Covid-19 pandemic will also be made, in order to anticipate the opportunities in Republic of North Macedonia for all citizens and businesses to use the digital transformation for a better and more prosperous life.